A kind of diamond abrasive wear-resistant floor material and preparation method thereof

By adding modified polytetrafluoroethylene and modified nylon fiber to the emery floor material, the problems of insufficient strength, poor wear resistance and weathering resistance of the existing emery floor materials are solved, and high strength and wear resistance are achieved. And improved weather resistance, suitable for long-term use in cold or hot areas.

CN118515458BActive Publication Date: 2025-01-21JIANGSU NANPU FLOORING ENG CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410583203.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-11
Publication Date
2025-01-21
Estimated Expiration
2044-05-11

Smart Images

  • Figure BDA0004834701720000101
    Figure BDA0004834701720000101
  • Figure BDA0004834701720000111
    Figure BDA0004834701720000111
Patent Text Reader

Abstract

The present invention provides a corundum wear-resistant floor material and a preparation method thereof, which comprises the following raw materials by weight: 30-40 parts of aggregate, 40-50 parts of silicate cement, 2-3 parts of modified polytetrafluoroethylene, 6-7 parts of modified nylon fiber, 5-7 parts of calcium aluminate cement, 4-5 parts of pigment, 7-11 parts of filler and 11-12 parts of water. Compared with the existing floor materials, the corundum wear-resistant floor material provided by the present invention has higher ground strength, high wear resistance and good weathering resistance, and improves the service life of the floor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of floor materials, and in particular relates to a diamond abrasion-resistant floor material and a preparation method thereof. Background Art

[0002] Diamond flooring is widely used in workshops, warehouses, factories and other places because of its convenient construction, pollution-free and low price. It has certain strength, hardness and weathering resistance. At present, diamond flooring materials mainly use diamond to make the floor surface hard, but in actual use, most of them have the following defects: 1. It cannot well enhance the strength of the floor, the wear resistance and tensile properties are not enough, it cannot well meet various collisions, and affects the stability and beauty of the floor; 2. The weathering resistance is poor, it is easy to absorb water, it is not heat-resistant and cold-resistant, and the corrosion resistance is poor.

[0003] In view of the above problems, the present field mostly adopts the improvement of the components of floor materials to solve them. Patent CN111635182A discloses a corundum wear-resistant floor material, which mainly includes the following components: cement, corundum, quartz sand, redispersible latex powder, carbon fiber, defoamer and iron oxide green. The prepared floor material has the advantages of wear resistance and pressure resistance, but it is necessary to add additional dispersing aids to disperse the materials. Patent CN114409319A discloses a tensile, wear-resistant and beautiful corundum wear-resistant floor material, which mainly includes the following components: corundum, quartz sand, epoxy resin, cement, iron oxide green, water reducer and inorganic salt. The corundum floor material has the advantages of tensile resistance, wear resistance, beauty and chemical corrosion resistance, but it does not take into account the problem of cracking and short life of the floor when used in cold or hot areas.

[0004] Therefore, there is an urgent need to develop a diamond abrasive wear-resistant floor material with high ground strength, wear resistance, weathering resistance and good dispersibility. Summary of the invention

[0005] In order to overcome the above-mentioned deficiencies of the prior art, the present invention provides a diamond abrasive wear-resistant floor material and a preparation method thereof. The present invention increases the weathering and corrosion resistance of the floor material by modifying polytetrafluoroethylene and modified nylon fiber, reduces the problem of slow drying of the floor after getting wet during use, and has high wear resistance.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] The first aspect of the present invention provides a diamond abrasive wear-resistant floor material, which comprises the following raw materials, by weight: 30-40 parts of aggregate, 40-50 parts of silicate cement, 2-3 parts of modified polytetrafluoroethylene, 6-7 parts of modified nylon fiber, 5-7 parts of calcium aluminate cement, 4-5 parts of pigment, 7-11 parts of filler and 11-12 parts of water.

[0008] In some embodiments, the method for preparing the modified polytetrafluoroethylene comprises the following steps:

[0009] A1. Soak polytetrafluoroethylene in nitric acid solution for 23-25 ​​hours, wash, and vacuum dry at 50-60°C for 6-8 hours to obtain active polytetrafluoroethylene;

[0010] A2, dissolving (3-glycidyl propoxy) trimethoxy silane in a mixture of ethanol and deionized water, adjusting the pH to 1.8-2.2 with nitric acid, stirring at 65-75° C. for 11-13 h, then adding active polytetrafluoroethylene and nano-silica sol colloid, stirring at 65-75° C. for 24-25 h, to obtain a solid-liquid mixture;

[0011] A3. Add ethylenediamine to the solid-liquid mixture obtained in step A2, stir at 38-42° C. for 3.5-4.5 h, and after the reaction is completed, perform rotary evaporation, vacuum dry at 110-120° C. for 10-12 h, and then calcine at 200-250° C. for 1-2 h to obtain the modified polytetrafluoroethylene.

[0012] Preferably, the method for preparing the modified polytetrafluoroethylene comprises the following steps:

[0013] A1. Soak polytetrafluoroethylene in nitric acid solution for 24 hours, wash, and vacuum dry at 55°C for 7 hours to obtain active polytetrafluoroethylene;

[0014] A2, dissolving (3-glycidyl propoxy) trimethoxy silane in a mixture of ethanol and deionized water, adjusting the pH to 2 with nitric acid, stirring at 70° C. for 12 h, then adding active polytetrafluoroethylene and nano-silica sol colloid, stirring at 70° C. for 24 h, to obtain a solid-liquid mixture;

[0015] A3. Add ethylenediamine to the solid-liquid mixture obtained in step A2, stir at 40° C. for 4 h, and after the reaction is completed, perform rotary evaporation, vacuum dry at 115° C. for 11 h, and then calcine at 220° C. for 1.5 h to obtain the modified polytetrafluoroethylene.

[0016] Polytetrafluoroethylene has excellent heat resistance and cold resistance, can be used for a long time at -180-260℃, and has the characteristics of acid and alkali resistance and resistance to various organic solvents. It can be used in floor materials to improve the heat resistance, cold resistance and corrosion resistance of the floor. However, the strong electronegativity of fluoride ions in polytetrafluoroethylene reduces the polarity of the entire molecule, and the interaction force between the fluoride ions and water molecules is small, making it difficult to disperse evenly in water. The present invention solves the technical problem that polytetrafluoroethylene is difficult to disperse by modifying polytetrafluoroethylene and wrapping a dense layer of silicon dioxide on the surface of polytetrafluoroethylene. In addition, after being dispersed in the entire system, it is affected by the alkalinity of the entire system. During use, silicon dioxide slowly decomposes into silicates, which can be used as a gelling agent for floor materials, increase the bonding force between the raw materials of floor materials, and increase the firmness of the floor.

[0017] In some embodiments, the concentration of the nitric acid solution in step A1 is 80 wt %.

[0018] In some embodiments, the mass ratio of (3-glycidylpropoxy)trimethoxysilane to the nano-silica sol colloid in step A2 is 1:(120-125).

[0019] Preferably, in step A2, the mass ratio of (3-glycidylpropoxy)trimethoxysilane to the nano-silica sol colloid is 1:124.

[0020] In some embodiments, the mass ratio of the solid-liquid mixture to ethylenediamine in step A3 is (1498-1501):1.

[0021] Preferably, in step A3, the mass ratio of the solid-liquid mixture to ethylenediamine is 1499.3:1.

[0022] The mass ratio of the solid-liquid mixture to ethylenediamine is limited to promote the ring opening of epoxy groups in the solid-liquid mixture, react with the nano-silica sol colloid, and generate high-purity nano-silica particles on the surface of polytetrafluoroethylene.

[0023] In some embodiments, the mass fraction of nano-silica in the nano-silica sol colloid in step A2 is 30%.

[0024] The present invention does not impose any special restrictions on the source of the nano-silica sol colloid, which can be purchased from commercial sources, including but not limited to the nano-silica sol colloid purchased from S-Chemtech Co., Ltd. of South Korea.

[0025] The present invention does not impose any special restrictions on the source of the polytetrafluoroethylene, which can be purchased from the market, including but not limited to the polytetrafluoroethylene purchased from Shenyang Tianyuxiang Micro Powder Material Factory, model N06.

[0026] In some embodiments, the mass fraction of nitric acid in the preparation method of modified polytetrafluoroethylene is 60%.

[0027] In some embodiments, the method for preparing the modified nylon fiber comprises the following steps:

[0028] B1. Dissolve dodecanedioic acid in deionized water, slowly add hydrazine dropwise at 85-95°C while stirring, and react for 2-3h to obtain a crude product;

[0029] B2. The crude product obtained in step B1 is put into a reaction device, and deionized water is added, the reaction device is evacuated, and nitrogen is then charged to balance the pressure in the reaction device to atmospheric pressure. The temperature is gradually raised to 200-220° C., and the pressure in the reaction device is maintained at 1.5-2.5 MPa. The reaction is carried out for 1.8-2.2 hours. The temperature is further raised to 245-255° C., and the exhaust is performed. During the heating and exhaust process, the reaction pressure is maintained at 1.5-2.0 MPa. After the temperature reaches 245-255° C., the exhaust is closed to maintain the pressure at 1.5-2.0 MPa. After 1-1.5 hours, the air is discharged to normal pressure, the water in the system is discharged, the material is evacuated, the material is discharged, the pelletizing is performed, and the modified nylon fiber is obtained.

[0030] Preferably, the method for preparing the modified nylon fiber comprises the following steps:

[0031] B1. Dissolve dodecanedioic acid in deionized water, slowly add hydrazine dropwise at 90°C while stirring, and react for 2.5 hours to obtain a crude product;

[0032] B2. The crude product obtained in step B1 is put into a reactor, and deionized water is added. The system is evacuated to 0.1 MPa, and then nitrogen is charged to 0.2 MPa. The pressure in the reactor is balanced to atmospheric pressure. The temperature is gradually raised to 210° C., and the pressure in the reactor is maintained at 1.5-2.5 MPa. The reaction is carried out for 2 hours. The temperature is further raised to 250° C., and the exhaust is performed. During the heating and exhaust process, the reaction pressure is maintained at 1.5-2.0 MPa. After the temperature reaches 250° C., the exhaust is closed to maintain the pressure at 1.5-2.0 MPa. After 1.2 hours, the system is vented to normal pressure, the water in the system is discharged, and the system is evacuated to -0.05 MPa. The material is discharged, pelletized, and extracted to obtain modified nylon fiber.

[0033] In some embodiments, the mass ratio of dodecanedioic acid to hydrazine in step B1 is (7.2-8.6):1.

[0034] Preferably, in step B1, the mass ratio of dodecanedioic acid to hydrazine is 7.9:1.

[0035] Nylon fiber has the characteristics of high strength, high wear resistance, corrosion resistance, etc., so it is widely used in many fields. Usually, the tensile strength is highest in the dry state. As the humidity increases, the tensile strength decreases. The water absorption of nylon fiber is mainly due to the hydrogen bond between the amide group and water. People often physically blend nylon fiber with inorganic fillers or hydrophobic resins or perform bulk modification through molecular structure design to reduce its water absorption. The present invention prepares a modified nylon fiber by using dodecanedioic acid and hydrazine. When preparing the floor material, due to the presence of a large amount of water in the raw materials, the amide groups of the modified nylon fiber are more likely to form hydrogen bonds with water, and can be well dispersed during the preparation process. The carboxyl group of the nylon fiber has an adsorption effect on calcium carbonate in the filler, so that the filler and the nylon fiber can be evenly mixed, thereby increasing the firmness of the floor. After the floor is cured, the structure is dense, and in daily use, the area where a large amount of water directly contacts the nylon fiber is very small. Since the two amide groups of the nylon fiber are directly connected, and the long alkyl chain shields the formation of hydrogen bonds between water and the amide group, the drying speed of the floor is accelerated after it is wetted.

[0036] In some embodiments, the mass ratio of corundum to quartz sand in the aggregate is (0.9-1.1):1.

[0037] Preferably, the mass ratio of corundum to quartz sand in the aggregate is 1:1.

[0038] In the present invention, both corundum and quartz sand are natural mineral sand particles with high hardness and wear resistance. As aggregates of floor materials, the hardness and wear resistance of the floor are increased by adjusting the ratio of the two. In addition, in order to ensure the flatness and aesthetics of the floor, the particle size of the quartz sand should be between 0.1mm and 0.3mm; silicate cement is used as a gelling agent and aluminate cement is used as a coagulant. The coordinated use of the two shortens the setting time of the floor.

[0039] In some embodiments, the filler comprises limestone powder and anhydrous gypsum in a mass ratio of (5-7): (2-4).

[0040] In some embodiments, the pigment comprises iron oxide green.

[0041] A second aspect of the present invention provides a method for preparing a diamond wear-resistant floor material, comprising the following steps:

[0042] (1) Aggregate, silicate cement, modified polytetrafluoroethylene, modified nylon fiber, calcium aluminate cement, pigment and filler are stirred for 30-40 minutes to obtain a premix;

[0043] (2) adding water to the premix obtained in step (1), and continuing stirring for 15-30 minutes to obtain the diamond abrasive wear-resistant floor material.

[0044] Compared with the prior art, the present invention has the following beneficial effects:

[0045] 1. The present invention combines the raw materials of diamond abrasive wear-resistant floor materials: aggregate, silicate cement, modified polytetrafluoroethylene, modified nylon fiber, calcium aluminate cement, pigment and filler, and regulates the composition and proportion so that the obtained floor material can withstand greater ground pressure, resist acid, alkali and various organic solvents, has good ground strength, wear resistance and weathering resistance, and can be used in cold or hot areas;

[0046] 2. The present invention increases the dispersibility of polytetrafluoroethylene in water by modifying polytetrafluoroethylene. Affected by the alkalinity of the entire system, during use, silicon dioxide slowly decomposes into silicates, which can be used as a gelling agent for floor materials, increase the bonding force between the raw materials of the floor materials, and increase the firmness of the floor;

[0047] 3. The present invention prepares a modified nylon fiber by using dodecanedioic acid and hydrazine. When preparing the floor material, due to the presence of a large amount of water in the raw materials, the amide groups of the nylon fiber are more likely to form hydrogen bonds with water, and can be well dispersed during the preparation process. The carboxyl group of the nylon fiber has an adsorption effect on the calcium carbonate in the filler, so that the filler and the nylon fiber can be mixed evenly, thereby increasing the firmness of the floor. The floor has a dense structure after solidification, and in daily use, the area where a large amount of water directly contacts the nylon fiber is very small. In addition, since the two amide groups of the nylon fiber are directly connected, and the long alkyl chain shields the formation of hydrogen bonds between water and the amide group, the floor dries faster after being wetted. DETAILED DESCRIPTION

[0048] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following examples and comparative examples are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.

[0049] In order to facilitate those skilled in the art to implement the present invention, some raw materials and manufacturers of the embodiments and comparative examples are described as follows:

[0050] Nano-silica sol colloid was purchased from S-Chemtech Co., Ltd., South Korea;

[0051] Polytetrafluoroethylene was purchased from Shenyang Tianyuxiang Micro Powder Material Factory, model N06;

[0052] Nylon 66 was purchased from Dongguan Mingsheng Plastic Raw Materials Co., Ltd.;

[0053] POE-g-MAH and GR216 were purchased from DuPont, USA.

[0054] Preparation Example 1

[0055] The preparation method of modified polytetrafluoroethylene-A comprises the following steps:

[0056] A1. Soak 60g of polytetrafluoroethylene in a nitric acid solution for 24h, wash with deionized water, and vacuum dry at 55°C for 7h to obtain active polytetrafluoroethylene;

[0057] A2, 3.6g (3-glycidyl propoxy) trimethoxy silane was dissolved in a mixture of 150g ethanol and 150g deionized water, pH=2 was adjusted with nitric acid, and stirred at 70°C for 12h, then active polytetrafluoroethylene and 446g nano silica sol colloid were added, and stirred at 70°C for 24h to obtain a solid-liquid mixture;

[0058] A3. Add 0.54 g of ethylenediamine to the solid-liquid mixture obtained in step A2, stir at 40° C. for 4 h, and after the reaction is completed, rotary evaporate, vacuum dry at 115° C. for 11 h, and then calcine at 220° C. for 1.5 h to obtain the modified polytetrafluoroethylene.

[0059] Preparation Example 2

[0060] The preparation method of modified polytetrafluoroethylene-B comprises the following steps:

[0061] A1. Dissolve 3.6 g (3-glycidyl propoxy) trimethoxysilane in a mixture of 150 g ethanol and 150 g deionized water, adjust the pH to 2 with nitric acid, stir at 70° C. for 12 h, then add commercially available polytetrafluoroethylene and 446 g nano silica sol colloid, stir at 70° C. for 24 h to obtain a solid-liquid mixture;

[0062] A2. Add 0.54 g of ethylenediamine to the solid-liquid mixture obtained in step A1, stir at 40° C. for 4 h, and after the reaction is completed, rotary evaporate, vacuum dry at 115° C. for 11 h, and then calcine at 220° C. for 1.5 h to obtain the modified polytetrafluoroethylene.

[0063] Preparation Example 3

[0064] The preparation method of modified nylon fiber-1 comprises the following steps:

[0065] B1. Dissolve 7.9 g of dodecanedioic acid in 100 g of deionized water, slowly add 1 g of hydrazine at 90°C while stirring, and react for 2.5 h to obtain a crude product;

[0066] B2. The crude product obtained in step B1 was put into a reactor, and 200 g of deionized water was added. The system was evacuated to 0.1 MPa, and then filled with nitrogen to 0.2 MPa. The pressure in the reactor was balanced to atmospheric pressure. The temperature was gradually raised to 210°C, and the pressure in the reactor was maintained at 1.5-2.5 MPa. The reaction was continued for 2 hours. The temperature was continued to be raised to 250°C, and the exhaust was performed. During the heating and exhaust process, the reaction pressure was maintained at 1.5-2.0 MPa. After the temperature reached 250°C, the exhaust was closed to maintain the pressure at 1.5-2.0 MPa. After 1.2 hours, the system was vented to normal pressure, the water in the system was discharged, the system was evacuated to -0.05 MPa, the material was discharged, pelletized, and extracted to obtain modified nylon fiber-1.

[0067] Preparation Example 4

[0068] The preparation method of modified nylon fiber-2 is the same as that of Preparation Example 3, except that 1 g of hydrazine is replaced by 1.88 g of ethylenediamine.

[0069] Preparation Example 5

[0070] The preparation method of modified nylon fiber-3 comprises the following steps:

[0071] 10 g of nylon 66 and 1 g of POE-g-MAH were mixed in a high-speed kneader, and then added into a twin-screw extruder, extruded at 240° C. and a screw speed of 300 r / min to obtain modified nylon fiber-3.

[0072] Example 1

[0073] A diamond abrasive wear-resistant floor material comprises the following raw materials, measured by weight: 36 parts of aggregate, 45 parts of silicate cement, 2.5 parts of modified polytetrafluoroethylene-A, 16.5 parts of modified nylon fiber-, 6 parts of calcium aluminate cement, 4.5 parts of iron oxide green, 9 parts of filler and 11.5 parts of water.

[0074] The aggregate includes 18 parts of diamond and 18 parts of quartz sand, and the filler includes 6 parts of limestone and 3 parts of anhydrous gypsum.

[0075] Among them, modified polytetrafluoroethylene-A is prepared by Preparation Example 1, and modified nylon fiber-1 is prepared by Preparation Example 3.

[0076] The preparation steps of the diamond wear-resistant floor material of this embodiment are as follows:

[0077] (1) Aggregate, silicate cement, modified polytetrafluoroethylene-A, modified nylon fiber-1, calcium aluminate cement, iron oxide green and filler are stirred for 35 minutes to obtain a premix;

[0078] (2) adding water to the premix obtained in step (1), and continuing stirring for 25 minutes to obtain the diamond abrasive wear-resistant floor material.

[0079] Example 2

[0080] A diamond abrasive wear-resistant floor material comprises the following raw materials, measured by weight: 30 parts of aggregate, 40 parts of silicate cement, 2 parts of modified polytetrafluoroethylene-A, 6 parts of modified nylon fiber-1, 5 parts of calcium aluminate cement, 4 parts of iron oxide green, 7 parts of filler and 11 parts of water.

[0081] The aggregate includes 15 parts of diamond and 15 parts of quartz sand, and the filler includes 5 parts of limestone and 2 parts of anhydrite.

[0082] Among them, modified polytetrafluoroethylene-A is prepared by Preparation Example 1, and modified nylon fiber-1 is prepared by Preparation Example 3.

[0083] The preparation steps of the diamond wear-resistant floor material of this embodiment are as follows:

[0084] (1) Aggregate, silicate cement, modified polytetrafluoroethylene-A, modified nylon fiber-1, calcium aluminate cement, iron oxide green and filler are stirred for 30 minutes to obtain a premix;

[0085] (2) adding water to the premix obtained in step (1), and continuing stirring for 15 minutes to obtain the diamond abrasive wear-resistant floor material.

[0086] Example 3

[0087] A diamond abrasive wear-resistant floor material comprises the following raw materials, measured by weight: 40 parts of aggregate, 50 parts of silicate cement, 3 parts of modified polytetrafluoroethylene-A, 7 parts of modified nylon fiber-1, 7 parts of calcium aluminate cement, 5 parts of iron oxide green, 11 parts of filler and 12 parts of water.

[0088] The aggregate includes 20 parts of diamond and 20 parts of quartz sand, and the filler includes 7 parts of limestone and 4 parts of anhydrite.

[0089] Among them, modified polytetrafluoroethylene-A is prepared by Preparation Example 1, and modified nylon fiber-1 is prepared by Preparation Example 3.

[0090] The preparation steps of the diamond wear-resistant floor material of this embodiment are as follows:

[0091] (1) Aggregate, silicate cement, modified polytetrafluoroethylene-A, modified nylon fiber-1, calcium aluminate cement, iron oxide green and filler are stirred for 40 minutes to obtain a premix;

[0092] (2) adding water to the premix obtained in step (1), and continuing stirring for 30 minutes to obtain the diamond abrasive wear-resistant floor material.

[0093] Example 4

[0094] The diamond abrasive wear-resistant floor material and preparation method thereof of this embodiment have the same specific implementation method as Example 1, except that modified polytetrafluoroethylene-A is replaced by an equal mass portion of modified polytetrafluoroethylene-B, and modified polytetrafluoroethylene-B is prepared by Preparation Example 2.

[0095] Example 5

[0096] The diamond abrasion wear-resistant floor material and preparation method thereof of this embodiment have the same specific implementation method as Example 1, except that the modified nylon fiber-1 is replaced by an equal mass portion of modified nylon fiber-2, and the modified nylon fiber-2 is prepared by Preparation Example 4.

[0097] Example 6

[0098] The diamond abrasive wear-resistant floor material and preparation method thereof of this embodiment have the same specific implementation method as Example 1, except that the modified nylon fiber-1 is replaced by an equal mass portion of modified nylon fiber-3, and the modified nylon fiber-3 is prepared by Preparation Example 5.

[0099] Comparative Example 1

[0100] The diamond abrasive wear-resistant floor material and preparation method thereof of this comparative example have the same specific implementation manner as Example 1, except that the modified polytetrafluoroethylene-A is replaced by an equal mass portion of commercially available polytetrafluoroethylene.

[0101] Comparative Example 2

[0102] The diamond abrasion wear-resistant floor material and preparation method thereof of this embodiment are similar in specific implementation to that of Embodiment 1, except that the modified nylon fiber-1 is replaced by an equal mass portion of commercially available nylon 66.

[0103] Performance Testing:

[0104] The diamond abrasive wear-resistant floor materials of Examples 1-6 and Comparative Examples 1-2 were poured into a cubic mold with a side length of 150 mm and the mixture was vibrated and compacted using an electric vibration table. The molds were removed after 24 hours and cured for 28 days at a temperature of 20°C and a relative humidity of 95% to obtain test blocks, which were tested according to the following test method.

[0105] 1. Flexural strength

[0106] The flexural strength of the test blocks of the diamond abrasive wear-resistant floor materials of Examples 1-6 and Comparative Examples 1-2 was tested. According to the Standard for Test Methods of Mechanical Properties of Ordinary Concrete GB / T50081-2019, the flexural strength of the test blocks was tested using an MTS-800 electro-hydraulic universal testing machine;

[0107] 2. Compressive strength

[0108] The compressive strength of the test blocks of the diamond abrasive wear-resistant floor materials of Examples 1-6 and Comparative Examples 1-2 was tested. According to the Standard for Test Methods of Mechanical Properties of Ordinary Concrete GB / T50081-2019, the compressive strength of the test blocks was tested using a YAW-3000 microcomputer-controlled fully automatic concrete pressure testing machine;

[0109] 3. Wear resistance

[0110] With reference to the "Testing Procedures for Cement and Cement Concrete for Highway Engineering" (JTG 3420-2020), the test specimens were placed in a 60°C constant temperature oven for 12 hours to dry the specimens, and then the tests were carried out under 200N and 300N abrasion loads respectively. The test equipment used was a TMS-400 cement concrete abrasion testing machine, and the wear resistance was measured using the wear loss per unit area G c The results are shown in Table 1, and the calculation formula is as follows:

[0111] G c =(m1-m2) / 0.0125

[0112] Where: G c is the wear amount per unit area, kg / m 2 ;

[0113] m1 is the initial mass of the test block before wear, kg;

[0114] m2 is the mass of the test block after wear, kg;

[0115] 0.0125 is the wear area of ​​the test block, m 2 ;

[0116] 4. Freeze-thaw cycle

[0117] The test blocks made of the diamond abrasive wear-resistant floor of Examples 1-6 and Comparative Examples 1-2 were tested using a multifunctional building material freeze-thaw tester (HC-JCD), and the cycle test was repeated 10 times. The mass of the test blocks before and after the cycle was recorded, and the mass loss rate was calculated. The mass loss rate = (mass before the test - mass after the test) / mass before the test × 100%, and the compressive strength of the test blocks after the freeze-thaw cycle test was tested, and the compressive strength loss rate was calculated. The compressive strength loss rate = (compressive strength before the test - compressive strength after the test) / compressive strength before the test × 100%;

[0118] 5. Impermeability

[0119] Refer to the step-by-step pressure method in the "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete" (GB / T50082-2009) to test the impermeability grade of the test block using a concrete impermeability tester;

[0120] 6. Corrosion resistance

[0121] With reference to the Standard Test Method for Long-term Performance and Durability of Ordinary Concrete (GB / T50082-2009), 15 mL of 3 mol / L sulfuric acid solution was sprayed on the surface of the test block and allowed to stand for 24 hours, and then washed with water until the washing liquid was neutral. 15 mL of 3 mol / L sodium hydroxide solution was sprayed on the surface of the test block and allowed to stand for 24 hours, and then washed with water until the washing liquid was neutral. Dry at 40°C for 48 hours, record the mass of the test block before and after the test, and evaluate its corrosion performance with the mass loss rate.

[0122] The test results are shown in Table 1.

[0123] Table 1

[0124]

[0125]

[0126] From the test data of the diamond abrasive wear-resistant floor material obtained in Examples 1-3 in Table 1, it can be seen that by changing the ratio between the raw materials, the floor material has good flexural strength, compressive strength, corrosion resistance, impermeability, wear resistance and freeze-thaw resistance; Example 4 uses the same mass of modified polytetrafluoroethylene-B instead of modified polytetrafluoroethylene-A, which may make the combination between silica and active polytetrafluoroethylene more dense, resulting in a more uniform dispersion of modified polytetrafluoroethylene, thereby improving the corrosion resistance and freeze-thaw cycle resistance of the floor material; Example 5 uses the same mass of modified nylon fiber-2 instead of modified nylon fiber-1, and the presence of two methylene groups between the two amide groups, the long distance prevents the formation of hydrogen bonds between the amide groups, and it is easy to absorb water in the environment, so that the floor The anti-seepage grade of the floor decreases; in Example 6, since the modified nylon fiber-3 is used instead of the modified nylon fiber-1 with the same mass, the physically blended hydrophobic segments reduce the water absorption rate of the nylon fiber to a certain extent, but due to the different molecular structures, they are not completely compatible, and phase separation may occur, causing the floor to crack and affecting the compressive resistance of the floor; in Comparative Example 1, since the commercially available polytetrafluoroethylene is used instead of the modified polytetrafluoroethylene-A with the same mass, due to the poor dispersibility of the commercially available polytetrafluoroethylene, it may settle during the curing process of the floor, resulting in uneven distribution, causing the corrosion resistance and anti-freeze-thaw cycle performance to decrease; in Comparative Example 2, since the commercially available nylon 66 is used instead of the modified nylon fiber-1, the unmodified nylon fiber has a high water absorption, and may absorb water in the environment, affecting the anti-seepage performance of the floor and causing the anti-seepage grade to decrease.

[0127] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. A diamond abrasive wear-resistant floor material, characterized in that: The composition comprises the following raw materials by weight: 30-40 parts of aggregate, 40-50 parts of silicate cement, 2-3 parts of modified polytetrafluoroethylene, 6-7 parts of modified nylon fiber, 5-7 parts of calcium aluminate cement, 4-5 parts of pigment, 7-11 parts of filler and 11-12 parts of water; The preparation method of the modified polytetrafluoroethylene comprises the following steps: A1. Soak polytetrafluoroethylene in nitric acid solution for 23-25 ​​hours, wash, and vacuum dry at 50-60°C to obtain active polytetrafluoroethylene; A2, dissolving (3-glycidyl propoxy) trimethoxy silane in a mixture of ethanol and deionized water, adjusting the pH to 1.8-2.2 with nitric acid, stirring at 65-75°C for 11-13h, then adding active polytetrafluoroethylene and nano-silica sol colloid, stirring at 65-75°C for 24-25h, to obtain a solid-liquid mixture; A3, adding ethylenediamine to the solid-liquid mixture obtained in step A2, stirring at 38-42°C for 3.5-4.5h, after the reaction is completed, rotary evaporation, vacuum drying at 110-120°C for 10-12h, and then calcining at 200-250°C for 1-2h to obtain modified polytetrafluoroethylene; The preparation method of the modified nylon fiber comprises the following steps: B1. Dissolve dodecanedioic acid in deionized water, slowly add hydrazine dropwise at 85-95°C while stirring, and react for 2-3 hours to obtain a crude product; B2, the crude product obtained in step B1 is put into a reaction device, and deionized water is added, vacuumized, and then filled with nitrogen, the pressure in the reaction device is balanced to atmospheric pressure, the temperature is gradually increased to 200-220° C., the pressure in the reaction device is maintained at 1.5-2.5 MPa, the reaction is carried out for 1.8-2.2 hours, the temperature is continued to be increased to 245-255° C., and the exhaust is carried out. During the heating and exhaust process, the reaction pressure is maintained at 1.5-2.0 MPa. After the temperature reaches 245-255° C., the exhaust is closed to maintain the pressure at 1.5-2.0 MPa. After 1-1.5 hours, the air is discharged to normal pressure, the water in the system is discharged, vacuumized, discharged, pelletized, extracted, and modified nylon fiber is obtained; The aggregate comprises corundum and quartz sand in a mass ratio of (0.9-1.1):1; the filler comprises limestone powder and anhydrous gypsum in a mass ratio of (5-7):(2-4).

2. The diamond wear-resistant floor material according to claim 1, characterized in that: In the step A2, the mass ratio of (3-glycidylpropoxy)trimethoxysilane to the nano-silica sol colloid is 1:(120-125).

3. The diamond wear-resistant floor material according to claim 1, characterized in that: The mass ratio of the solid-liquid mixture to ethylenediamine in step A3 is (1498-1501):

1.

4. The diamond wear-resistant floor material according to claim 1, characterized in that: The mass ratio of dodecanedioic acid to hydrazine in step B1 is (7.2-8.6):

1.

5. The diamond wear-resistant floor material according to claim 1, characterized in that: The pigment is iron oxide green.

6. A method for preparing the diamond abrasive wear-resistant floor material according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Aggregate, silicate cement, modified polytetrafluoroethylene, modified nylon fiber, calcium aluminate cement, pigment and filler are stirred for 30-40 minutes to obtain a premix; (2) Add water to the premix obtained in step (1), and continue stirring for 15-30 minutes to obtain the diamond abrasive wear-resistant floor material.

Citation Information

Patent Citations

  • Carborundum wear-resistant floor material

    CN114409319A

  • Corrosion-resistant terrace

    CN104403510A

  • Carborundum wear-resistant floor material

    CN111635182A